Interdisciplinary semantic model for managing the design of a steam-assisted gravity drainage tooling system. Issue 1 (13th November 2017) - Leitch, Michael; Yusuf, Yishak; Ma, Yongsheng
Graphical abstract: Abstract: Complex engineering systems often require extensive coordination between different expert areas in order to avoid costly design iterations and rework. Cyber-physics system (CPS) engineering methods could provide valuable insights to help model these interactions and optimize the design of such systems. In this work, steam assisted gravity drainage (SAGD), a complex oil extraction process that requires deep understanding of several physical-chemical phenomena, is examined whereby the complexities and interdependencies of the system are explored. Based on an established unified feature modeling scheme, a software modeling framework is proposed to manage the design process of the production tools used for SAGD oil extraction. Applying CPS methods to unify complex phenomenon and engineering models, the proposed CPS model combines effective simulation with embedded knowledge of completion tooling design in order to optimize reservoir performance. The system design is expressed using graphical diagrams of the unified modelling language (UML) convention. To demonstrate the capability of this system, a distributed research group is described, and their activities coordinated using the described CPS model.